PERJANJIAN PEMBERIAN KUASA PENJUALAN BARANG DENGAN SISTEM COUNTER DI PERTOKOAN MALL SAMARINDA - Royani, Esti (STIH Awang Long Samarinda, 2018)
Agreement on authorizing the sale of goods by counter system shall initially be made by an agreement between the parties. The Supplier Party shall first apply with the goods custody clause to the Mall, which shall then proceed with an offer of all the terms of the agreement referred to by the Mall. After the supplier agrees to all terms specified by the supplirr party has agreed to the terms of the agreement, the agreement can be realized that is by the delivery of goods by the supplier at the Mall. The series of legal acts that can be legally qualified as an authorization action from the supplier. The parties have rights and obligations in accordance with the clauses that have been determined.